Instant Oyster Mushroom Congee - Faisal Akbar Zaenal; Syahrial; Abdi Nurul Mahsyar (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
This research is an experimental study that aims to determine: (1) The process of making instant oyster mushroom congee; (2) Panelists acceptance of the organoleptic of instant oyster mushroom congee, which includes color, aroma, texture, taste, and overall (overall assessment); (3) Potassium Nutritional Value of instant oyster mushroom congee. There were 38 panelists, consisting of 3 trained panelists, 25 semi-trained panelists, and 10 untrained panelists. The data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive analysis and ANOVA. The research was out at the Kitchen Laboratory Politeknik Pariwisata Makassar and the Makassar Health Laboratory Center. The results showed instant oyster mushroom congee products started from preparation, weighing, cutting, grinding, drying, storage and packaging. The panelists acceptance of the instant oyster mushroom congee with the F1 formulation with a yield of 1.5 grams of dry oyster mushrooms is equivalent to 15 grams of fresh oyster mushrooms. In terms of color, aroma, texture, and taste assessment, it is better than other formulations with a rating of 4.18, aroma, texture, and taste of 4.82, and overall, 5.42. The change in the nutritional value of potassium in instant oyster mushroom congee was 225.75 mcg, and the nutritional value of iron was 14.72 mcg.